Discharging dengue fever patients with low platelets can be safe - Devaraj, Navin Kumar (Ibn Sina Medical College, 2020)
This is an interesting case of Mr MS who presented with 7 days of fever, loss of appetite and lethargy. Physical examination was unremarkable. Investigation revealed a very low platelet of 11 x 109/L and haematocrit of 46%. He was managed as outpatient and recovered well despite this alarming low platelet level, proving not all dengue fever patients ,especially those with no warning signs and clinically well, needs hospital admission.